Postharvest wine grape dehydration: ethanol dissipation from grape and biochemical changes - Bianchi, Alessandro; Pettinelli, Stefano; Santini, Gregorio; Taglieri, Isabella; Zinnai, Angela; Petriccione, Milena; Magri, Anna; Modesti, Margherita; Cerreta, Raffaele; Bellincontro, Andrea (Journal of the science of food and agriculture, 2024)
BACKGROUND During postharvest dehydration, grapes are subject to metabolic changes including ethanol anabolism and catabolism. These changes affect the quality of the final product and ethanol production is a key step. Ethanol dissipation has never been measured during postharvest wine grape dehydration. Thus, the present study aimed to: (i) monitor ethanol dissipation and (ii) investigate chemical–biochemical changes in berries during dehydration. RESULTS Ethanol dissipation from Raboso grapes, under controlled postharvest dehydration, was found to comprise up to 36% of weight loss (w.l.). Moreover, the activity of enzymes involved in the anaerobic metabolism of grapes was investigated. Ethanol dissipation was highly correlated with grape weight loss (r2 = 0.989). Alcohol dehydrogenase activity, responsible for the reduction of ethanol to acetaldehyde, declined significantly with w.l. Similarly, pyruvate decarboxylase and lactate dehydrogenase reduced their activity. High lipoxygenase activity was measured at 27% w.l., whereas polyphenol oxidation was constant and declined in the last sampling. CONCLUSION Ethanol dissipation during postharvest dehydration allows for reducing anaerobic metabolism and promotes oxidative metabolism. The sensor used can be a useful commercial tool for monitoring berry metabolism. © 2023 Society of Chemical Industry.